Customized Multilevel 3D Printing Implant for Reconstructing Spine Tumor: A Retrospective Case Series Study in a Single Center. Issue 9 (27th July 2022) - Sun, Zhengwang; Yin, Mengchen; Sun, Yueli; Cheng, Mo; Fang, Meng; Huang, Wending; Ma, Junming; Yan, Wangjun
Abstract: Objective: To investigate the clinical efficacy and safety of 3D printed artificial vertebral body for patients who underwent multilevel total en bloc spondylectomy (TES) and analyze whether it could reduce the incidence of implant subsidence. Methods: This is a retrospective study. From January 2017 to May 2018, eight consecutive cases with spine tumor undergoing multilevel TES were analyzed. All patients underwent X‐ray and CT examinations to evaluate the stability of internal fixation during the postoperative follow‐up. Demographic, surgical details, clinical data, and perioperative complications was collected. Visual analog scale, Frankel score, and spinal instability neoplastic score (SINS) classification were also recorded. Results: There were six cases of primary spinal tumor and two cases of metastatic spinal tumor. All patients achieved remarkable pain relief and improvement in neurological function. Five patients underwent operation through the posterior approach, one patient underwent operation through the anterior approach and the remaining two patients through a combined anterior and posterior approach. At the last follow‐up period, X‐rays showed that the 3D printed artificial vertebral body of all cases matched well, and the fixation was reliable. Hardware failure such as loosening, sinking, breaking, and displacement wasn't observed during the follow‐up period. Conclusion: 3D printed customized artificial vertebral body can provide satisfying good clinical and radiological outcomes for patients who have undergone multilevel TES. Abstract : 1. The customized 3D printed artificial vertebral body was design to replace vertebral bodies to stabilize the spine column. Postoperative X‐ray showed a good radiographic outcome 3 months after operation. 2. Treatment and outcomes of eight patients who underwent multilevel TES. 3. A presentation of a typical case.